HUBUNGAN KEPEMIMPINAN, MOTIVASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA PERAWAT RAWAT INAP RSUD SIDIKALANG KABUPATEN DAIRI TAHUN 2018HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATA KULIAH ASKEB NIFAS DAN MENYUSUI MAHASISWI TINGKAT III DI UNIVERSITAS DA - FIKA LESTARI (JURNAL ILMIAH KOHESI, 2019)
Motivation is very important to improve learning outcomes, employment or activity would work better if accompanied by a willingness and support from others in order to focus and attention to achieve the goal. Ruling subjects Midwifery Care and Breastfeeding is one of the subjects of expertise obstetrics, this course provides the ability to implement comprehensive midwifery practice with care in an effective, safe and holistic attention to the cultural aspects of the post-partum and breastfeeding mothers. This study aimed to find out how strong the relationship between motivation to learn the results of student learning at the University Darma AgungYear 2016 Terrain.Quantitative research using analytical research design. The study population was a student at level II with a sampling technique that total sampling many as 41 people. Based on an analysis using Chi Square obtained no significant relationship with outcome intrinsic motivation to learn subjects Midwifery Care Postpartum and Breastfeeding 0,016 with p value <0.05 value of α, and obtained no significant relationship with extrinsic motivation learning outcomes subjects Midwifery Care parturition and Suckling with p value 0.413> 0.05 value of α. The results of this study that the motivation that is in itself a strong urge to get a good learning outcome, and if only there is support from the outside only then it will not succeed without a will in yourself. Expected to lecturers to be able to see the potential in themselves students a order to improve learning outcomes were good